The effect of a second runner on pacing strategy and RPE during a running time trial - Bath, D.; Turner, L. A.; Bosch, A. N.; Tucker, R.; Lambert, E. V.; Thompson, K. G.; St Clair Gibson, A. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The aim of this study was to examine performance, pacing strategy and perception of effort during a 5 km time trial while running with or without the presence of another athlete. Methods: Eleven nonelite male athletes participated in five 5 km time trials: two self-paced, maximal effort trials performed at the start and end of the study, and three trials performed in the presence of a second runner. In the three trials, the second runner ran either in front of the subject, behind the subject, or next to the subject. Performance times, heart rate, RPE, and a subjective assessment of the effect of the second runner on the athlete`s performance were recorded during each of the trials. Results: There was no significant difference in performance times, heart rate or RPE between any of the five trials. Running speed declined from the 1st to the 4th kilometer and then increased for the last kilometer in all five trials. Following the completion of all trials, 9 of the 11 subjects perceived it to be easier to complete the 5 km time trial with another runner in comparison with running alone. Conclusions: While the athletes perceived their performance to be improved by the presence of another runner, their pacing strategy, running speed, heart rate and RPE were not significantly altered. These findings indicate that an athlete`s subconscious pacing strategy is robust and is not altered by the presence of another runner.